ByzRev 06.2024.027: Stephanie Rumpza, Phenomenology of the Icon.: Mediating God through the Image. Cambridge: Cambridge University Press 2023. - Geréby, György (The Byzantine Review, 2024)
Stephanie Rumpza, Phenomenology of the Icon. Mediating God through the Image. Cambridge: Cambridge University Press 2023. 350 pp. – ISBN 978-1-009-31792-4